Method for improving strength of molybdenum and molybdenum alloy laser welding joint

By laying TiC powder on molybdenum and molybdenum alloy workpieces and laser welding, the problems of low strength and prone to cracks in the welded joints of molybdenum and molybdenum alloy are solved, and the tensile strength of the welded joints is significantly improved.

CN119733943APending Publication Date: 2025-04-01XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935265.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The welding joints of molybdenum and its alloys have low strength, especially the laser welding weld strength is only 20% of the rolled state, and it is prone to cracks, which limits its application in the engineering field.

Method used

TiC powder is uniformly coated in the area to be welded by molybdenum or molybdenum alloy workpiece, and laser welding is performed under a protective atmosphere, and then cooled to room temperature to increase the strength of the welded joint.

Benefits of technology

By doping TiC powder, the physical and chemical metallurgy processes during laser welding are changed, the generation of welding cracks is suppressed, the grains are refined, and the tensile strength of the welded joints is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733943A_ABST
    Figure CN119733943A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of welding, and particularly relates to a method for improving the strength of a molybdenum and molybdenum alloy laser welding joint, which comprises the following steps: paving TiC powder in a to-be-welded area of a workpiece, carrying out laser welding in a protective atmosphere, and cooling to room temperature to obtain the welding joint. Physical and chemical metallurgical processes in the laser welding process are changed, welding cracks disappear, and finally the tensile strength of a laser welding joint is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding, and in particular relates to a method for improving the strength of laser welded joints of molybdenum and molybdenum alloys. Background Art

[0002] Molybdenum and its alloys have broad application prospects in aerospace, nuclear energy industry, chemical industry and other fields due to their excellent high temperature strength, good thermal conductivity and corrosion resistance. However, the low strength of the welded joints of molybdenum alloys limits their application in the engineering field. The tensile strength of rolled molybdenum and molybdenum alloys is generally 600-700MPa, but the maximum strength of laser welded welds is only 20% of that of rolled ones, and cracks are prone to appear in the welds. The main reason for the low strength of the weld is the intrinsic brittleness and non-intrinsic brittleness of molybdenum. The non-intrinsic brittleness is mainly due to the segregation of impurity element oxygen at the grain boundaries. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to propose a method for improving the strength of laser welding joints of molybdenum and molybdenum alloys by doping TiC powder, which can inhibit the generation of welding cracks and improve the tensile strength of the joints.

[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0005] A method for improving the strength of laser welded joints of molybdenum and molybdenum alloys comprises the following steps:

[0006] S1. Pre-treat the area to be welded of the workpiece, where the workpiece is made of molybdenum or molybdenum alloy;

[0007] S2. Evenly spread TiC powder on the area to be welded;

[0008] S3. Perform laser welding under a protective atmosphere, then cool to room temperature to obtain a welded joint.

[0009] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, in step S1, the area to be welded of the workpiece is polished with 400-3000# sandpaper and then ultrasonically cleaned, and then dried in a drying oven at 70°C for 5-20 minutes.

[0010] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, wherein: in the step S1, ultrasonic cleaning is carried out in an alcohol solution, the number of ultrasonic cleanings is ≥3, and the time of each ultrasonic cleaning is ≥5 minutes.

[0011] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, in the step S1, after pre-treating the area to be welded of the workpiece, laser welding is performed within 30 minutes to prevent the area from being contaminated after the pre-treatment, thereby affecting the welding effect.

[0012] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, in step S1, the workpiece material is molybdenum, molybdenum-titanium-zirconium alloy, or molybdenum-rhenium alloy.

[0013] As a preferred embodiment of the method for improving the strength of molybdenum and molybdenum alloy laser welding joints described in the present invention, wherein: in the step S2, the workpiece is clamped in a glove box, and the TiC powder is evenly spread on the surface of the workpiece in the area to be welded, the TiC powder spreading length is the same as the displacement of the laser beam, the width is 1-3mm (the width is the same as the molten pool width, and the molten pool width depends on different heat inputs), and the thickness is 0.1-0.3mm.

[0014] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, in step S3, a protective gas is introduced into the glove box to perform laser welding, and the joint is cooled to room temperature for 2-5 minutes under the protective gas to obtain a welded joint.

[0015] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, in step S3, the shielding gas is argon gas with a purity greater than 99.9%.

[0016] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, in step S3, the laser power of laser welding is 800-1500W, and the welding speed is 0.8-1.2m / min.

[0017] As a preferred embodiment of the method for improving the strength of laser welded joints of molybdenum and molybdenum alloys described in the present invention, in step S3, the weld is in the form of butt welding, lap welding, or T-welding.

[0018] The beneficial effects of the present invention are as follows:

[0019] The present invention proposes a method for improving the strength of laser welded joints of molybdenum and molybdenum alloys, which includes covering the area of ​​the workpiece to be welded with TiC powder, performing laser welding under a protective atmosphere, and then cooling to room temperature to obtain a welded joint. The present invention changes the physical and chemical metallurgical processes of the laser welding process, and the welding cracks disappear, thereby ultimately improving the tensile strength of the laser welded joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0021] Figure 1 Schematic diagram of laser welding of molybdenum and molybdenum alloy plates.

[0022] Figure 2 This is a scan of the molten pool of the welding joint prepared in Example 1.

[0023] Figure 3 This is a scan of the molten pool of the welding joint prepared in Comparative Example 1.

[0024] Figure 4 This is the room temperature tensile curve of the welded joint prepared in Example 1.

[0025] Figure 5 This is the room temperature tensile curve of the welded joint prepared in Comparative Example 1.

[0026] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0027] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The main purpose of the present invention is to propose a method for improving the strength of laser welded joints of molybdenum and molybdenum alloys by doping TiC powder, which changes the physical and chemical metallurgical processes of the welded joints, inhibits the generation of welding cracks, refines the grains, and improves the tensile strength of the joints. For example, the tensile strength of the laser welded joints of Mo-14Re plates is ≥350MPa.

[0029] According to one aspect of the present invention, the present invention provides the following technical solution:

[0030] A method for improving the strength of laser welded joints of molybdenum and molybdenum alloys comprises the following steps:

[0031] S1. Pre-treat the area to be welded of the workpiece, where the workpiece is made of molybdenum or molybdenum alloy;

[0032] S2. Evenly spread TiC powder on the area to be welded;

[0033] S3. Perform laser welding under a protective atmosphere, then cool to room temperature to obtain a welded joint.

[0034] Preferably, in step S1, the workpiece is ground with 400-3000# sandpaper in the area to be welded and then ultrasonically cleaned, and then dried in a drying oven at 70°C for 5-20 minutes.

[0035] Preferably, in step S1, ultrasonic cleaning is performed in an alcohol solution, the number of ultrasonic cleanings is ≥3, and the time of each ultrasonic cleaning is ≥5 min.

[0036] Preferably, in step S1, after pre-treating the area to be welded of the workpiece, laser welding is performed within 30 minutes to prevent the pre-treated area from being contaminated again, thereby affecting the welding effect.

[0037] Preferably, in step S1, the workpiece material is molybdenum, molybdenum-titanium-zirconium alloy, or molybdenum-rhenium alloy.

[0038] Preferably, in step S2, the workpiece is clamped in a glove box, and TiC powder is evenly spread on the surface of the workpiece in the area to be welded, the TiC powder spreading length is the same as the displacement of the laser beam, the width is 1-3 mm (the width is the same as the molten pool width, and the molten pool width depends on different heat inputs), and the thickness is 0.1-0.3 mm.

[0039] Preferably, in step S3, a protective gas is introduced into the glove box to perform laser welding, and the weld is cooled to room temperature for 2-5 minutes under the protective gas to obtain a welded joint.

[0040] Preferably, in step S3, the protective gas is argon with a purity greater than 99.9%.

[0041] Preferably, in step S3, the laser power of laser welding is 800-1500 W, and the welding speed is 0.8-1.2 m / min.

[0042] Preferably, in step S3, the weld is in the form of butt welding, lap welding or T-type welding.

[0043] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0044] Example 1

[0045] A method for improving the strength of laser welded joints of molybdenum and molybdenum alloys, taking the laser welded joints of Mo-14Re plates (weld form is butt welding) as an example, comprises the following steps:

[0046] S1. Grind the workpiece to be welded with 400#, 800#, 1000#, and 1500# sandpapers in turn, and wash the polished workpiece in an alcohol solution for 3 times, 5 minutes each time. Then dry at 70℃ for 5 minutes.

[0047] S2. TiC powder is evenly spread on the area to be welded; the TiC powder spreading dimensions are: length dimension is 30 mm of laser beam displacement, width is 2 mm of molten pool width, and thickness is 0.2 mm.

[0048] S3. Introduce argon gas with a purity greater than 99.9% as a protective gas into the glove box for laser welding. The laser power of the laser welding is 1000 W and the welding speed is 1 m / min. Cool to room temperature for 3 minutes under the protective gas to obtain a welded joint.

[0049] Example 2

[0050] A method for improving the strength of laser welded joints of molybdenum and molybdenum alloys, taking the laser welded joints of Mo-14Re plates (weld form is butt welding) as an example, comprises the following steps:

[0051] S1. Grind the welding area of ​​the workpiece with 400#, 800#, 1000#, and 1500# sandpaper in turn, and wash the polished workpiece in an alcohol solution for 3 times, 10 minutes each time. Then dry at 70℃ for 20 minutes.

[0052] S2. TiC powder is evenly spread on the area to be welded; the TiC powder spreading dimensions are: length dimension is 30 mm of laser beam displacement, width is 3 mm of molten pool width, and thickness is 0.3 mm.

[0053] S3. Introduce argon gas with a purity greater than 99.9% as a protective gas into the glove box for laser welding. The laser power of the laser welding is 1500 W and the welding speed is 1 m / min. Cool to room temperature for 3 minutes under the protective gas to obtain a welded joint.

[0054] Example 3

[0055] A method for improving the strength of laser welded joints of molybdenum and molybdenum alloys, taking the laser welded joints of Mo-14Re plates (weld form is butt welding) as an example, comprises the following steps:

[0056] S1. Grind the welding area of ​​the workpiece with 400#, 800#, 1000#, and 1500# sandpaper in turn, and wash the polished workpiece in an alcohol solution for 4 times, 5 minutes each time. Then dry it at 70℃ for 10 minutes.

[0057] S2. TiC powder is evenly spread on the area to be welded; the TiC powder spreading dimensions are: length dimension is 30 mm of laser beam displacement, width is 1 mm of molten pool width, and thickness is 0.1 mm.

[0058] S3. Introduce argon gas with a purity greater than 99.9% as a protective gas into the glove box for laser welding. The laser power of the laser welding is 800 W and the welding speed is 1 m / min. Cool to room temperature for 3 minutes under the protective gas to obtain a welded joint.

[0059] Comparative Example 1

[0060] The difference from Embodiment 1 is that step S2 is not performed.

[0061] After the welding is completed, the tensile specimen and the metallographic specimen are cut in the welding area, the burrs of the tensile specimen are polished, and the metallographic specimen is polished, polished and corroded. The morphology of the metallographic specimens of Example 1 and Comparative Example 1 is observed, respectively. Figure 2 , Figure 3 As shown, Example 1 with TiC powder added had no crack defects and the grain boundaries were tightly bonded; Comparative Example 1 had obvious intergranular cracks. The tensile strength test of the tensile specimens of Examples 1-3 and Comparative Example 1 was performed at room temperature. The results of Example 1 and Comparative Example 1 were as follows: Figure 4 , Figure 5 As shown, the tensile strengths of the joints of Examples 1-3 are 389.69 MPa, 354.69 MPa, and 376.42 MPa, respectively, while the tensile strength of the joint of Comparative Example 1 is only 130.08 MPa. The joint strength of Example 1 is increased by about 200% compared with that of Comparative Example 1.

[0062] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for improving the strength of laser welded joints of molybdenum and molybdenum alloys, characterized in that: The steps include: S1. Pre-treat the area to be welded of the workpiece, where the workpiece is made of molybdenum or molybdenum alloy; S2. Evenly spread TiC powder on the area to be welded; S3. Perform laser welding under a protective atmosphere, then cool to room temperature to obtain a welded joint.

2. The method for improving the strength of molybdenum and molybdenum alloy laser welding joints according to claim 1, characterized in that: In the step S1, the workpiece to be welded is polished with 400-3000# sandpaper and then ultrasonically cleaned, and then dried in a drying oven at 70°C for 5-20 minutes.

3. The method for improving the strength of molybdenum and molybdenum alloy laser welding joints according to claim 2, characterized in that: In the step S1, ultrasonic cleaning is performed in an alcohol solution, the number of ultrasonic cleanings is ≥3, and the time of each ultrasonic cleaning is ≥5 minutes.

4. The method for improving the strength of laser welded joints of molybdenum and molybdenum alloys according to claim 1, characterized in that: In the step S1, the workpiece material is molybdenum, molybdenum-titanium-zirconium alloy, or molybdenum-rhenium alloy.

5. The method for improving the strength of laser welded joints of molybdenum and molybdenum alloys according to claim 1, characterized in that: In step S2, the workpiece is clamped in a glove box, and TiC powder is evenly spread on the surface of the workpiece in the area to be welded. The TiC powder spreading length is the same as the displacement of the laser beam, the width is 1-3 mm, and the thickness is 0.1-0.3 mm.

6. The method for improving the strength of laser welded joints of molybdenum and molybdenum alloys according to claim 1, characterized in that: In the step S3, a protective gas is introduced into the glove box to perform laser welding, and the laser welding is performed, and the laser welding is performed for 2-5 minutes under the protective gas to cool the laser welding to room temperature to obtain a welded joint.

7. The method for improving the strength of laser welded joints of molybdenum and molybdenum alloys according to claim 6, characterized in that: In the step S3, the protective gas is argon gas with a purity greater than 99.9%.

8. The method for improving the strength of laser welded joints of molybdenum and molybdenum alloys according to claim 6, characterized in that: In step S3, the laser power of laser welding is 800-1500W, and the welding speed is 0.8-1.2m / min.

9. The method for improving the strength of laser welded joints of molybdenum and molybdenum alloys according to claim 1, characterized in that: In step S3, the weld form is butt welding, lap welding, or T-type welding.